The Foundations of the Polish Study of Law on Sustainable Development in Environmental Protection and for Keeping International and Domestic Peace and Security (Thoughts on the 100th Anniversary of the Birth of Professor Karol Wolfke) - Równy, Kazimierz (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The Contribution refers to significant efforts, undertaken by the Polish authorities, concerning the protection of the surroundings in which mankind exists, both internationally and internally. At the same time it is hoped that they will also remind us of the intuitive prediction of further developments in the UN system made by Polish scholars, which led to the acceptance of the principle of sustainable development – that is, preventing the degradation of the environment “at the source of economic and social affairs”
Keywords: zrównoważony rozwój; ochrona środowiska; studium polskie